An Analysis of Factors Affecting on the Success of Natural Tourism Villages (Case Study at Kandri Nature Tourism Village, Semarang City) - Titik Kurniawati; Mahfudz Mahfudz (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out the factors that influence the success of a tourist village. Qualitative methods were used in this study with a case study approach. The data was collected through in-depth interviews conducted in person and online with participants as well as direct observations conducted as supporting materials. The results of this study show that there are severalfactors that influence the success of tourism villages, namely the participation of local communities and communities in developing tourism villages, marketing activities carried out to attract tourists to visit there, sufficient funding to support tourism activities, networking with relations so that they can cooperate. The efforts made to achieve this success, namely tourismactivists as the main motorbikes in tourism villages must have a common vision, totality and solidarity in driving tourism village activities, hubungan managers with the general public must be well fostered, intensify marketing activities so that many tourists visit andbenefit thenetwork of relationships to get investors or sources of funds and media marketing.